De quoi les entreprises libérées sont-elles le nom ? - Thibaud Brière; Thomas Coutrot; Danièle Linhart (La Nouvelle Revue du Travail)
A number of so-called « liberated » companies claim for some time now that they have discovered a new way of operating, organising themselves, managing people and making decisions – a modus operandi characterised by greater horizontality, democracy and support for initiatives launched by staff members whose own well-being has supposedly also become more of a priority. Questions remain, however, as to the validity of such claims, specifically whether the rhetorical aspiration of worker emancipation reflects the actual outcomes ; whether the companies in question are anything other than a new avatar of post-Taylorist capitalism ; if the adaptation they incarnate are at best peripheral ; if they respond to new worker aspirations or embody actual managerial innovation ; and if this paradigm shift accurately represents the future of companies – in short, whether liberated companies keep their promises or are shams. The present paper speaks to all these debates.